The Effect of Antenatal Maternal Anxiety, Depression, and Stress on Infant Development at 6 Months of Age - Zahra Nafei; Razieh Fallah; Marzie Vaghefi; Zahra Rezaei; Tahereh Sadeghieh (Mashhad University of Medical Sciences, 2023)
Background: Mental disorders can significantly impact maternal health and neonatal health and development. This study investigated maternal anxiety, depression, and stress during pregnancy concerning their children's development.Methods: In this follow-up study, all pregnant women with gestational age > 12 weeks referring to an obstetrics and gynecology clinic affiliated with Shahid Sadoughi University of Medical Sciences over six months were included. Data on mothers were collected using a personal information questionnaire and the Depression Anxiety Stress Scale (DASS)-42 standard questionnaire. Finally, based on the inclusion and exclusion criteria, the children of 73 mothers were included in the study. Infant development was assessed based on the Persian version of the Ages and Stages Questionnaire (ASQ) at six months postpartum.Data analysis was conducted using the Pearson correlation test and multiple regression analysis. Statistical analyzes were carried out using SPSS 21. A P-value <0.05 was considered statistically significant.Results: In this study, 39.7%, 63%, and 56.2% of women suffered from depression, anxiety, and stress, respectively. In this study, a significant relationship was found between antenatal maternal depression and gross motor (P: 0.022), fine motor (P: 0.003), personal-social (P: 0.009), and communication skills (P: 0.0180). Moreover, there was a significant relationship between maternal anxiety and personal-social (P: 0.012) and gross motor domains (P: 0.008). Also, a significant association was observed between personal-social skills and maternal stress (P: 0.030).Conclusion: As shown by the results, antenatal maternal mental illness can interfere with the development of children. Therefore, paying attention to the mental health of pregnant women is necessary.